Penataan Pasar Rakyat dan Pasar Modern di Kota Surabaya - Ignatia Martha H; Nuruni Ika K W (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
The people's market plays an important role in supporting the distribution of goods and services in Surabaya. But its existence is increasingly pressured by the increasing number of modern markets (minimarkets) which continue to increase every year, which for the past seven years (2012-2017) numbered 729 units. The largest number are in strategic areas. And the existence of minimarkets has entered settlements. This study aims to enable the people's market and modern market as a result of the fact that the presence of the modern market in Surabaya is quite significant and is spread throughout the Surabaya region, which has a negative impact on the people's market, especially in terms of income and turnover.